Implementasi Mata Kuliah Pendidikan Multikultural - Muhammad Bahauddin Haidar (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to explore the perceptions of STAI Al-Hidayat Lasem students regarding the implementation of Multicultural Education courses as an effort to instill multicultural values in Rembang Regency, characterized by diverse ethnicities, religions, cultures, races, and ethnicities. With a vision and mission promoting multiculturalism, the university incorporates this concept into the curriculum to prevent potential conflicts. A qualitative research approach with a descriptive design was employed through interviews with semester students at STAI Al-Hidayat Lasem. Secondary data were gathered from scholarly journals and books. The findings reveal that students view multiculturalism as harmonization and mutual understanding. The implementation of the course creates an environment without discrimination, with fair and consultative teaching approaches. Institutional support is evident through collaboration, gender sensitivity, orientation of student organizations, and harmonious relationships between faculty and students. This abstract summarizes the main research findings on students' perceptions of the implementation of Multicultural Education at STAI Al-Hidayat Lasem.